Interacting Protein Domains: Their Role in Signal and Energy Transduction - Heilmeyer, Ludwig M. G. (NATO ASI series / H, 1997)
The understanding of cellular signaling - in eukaryotes mainly carried out by reversible protein phosphorylation - depends on knowledge of the three-dimensional structure of signaling molecules, i.e. proteins. Many aspects of studying proteins at the atomic level are discussed, e.g. advances in the determination of protein structure by X-ray diffraction methods, spectroscopical studies, and time-resolved Fourier transform (FTIR) spectroscopy. An area in which a quantum step in the development has occurred is the characterization of a single motor molecule, myosin. For the first time a completely new method - the application of laser traps - is available to assay the activity of a single motor molecule. A discussion of these methods is included in this book